2021
DOI: 10.1002/chem.202100912
|View full text |Cite
|
Sign up to set email alerts
|

Endohedral Mixed Aggregates: Sodium Alkoxide Cages with Organic or Inorganic Central Anions and Variable Hull

Abstract: Alkali metal alkoxides are widely used in chemistry due to their Brønsted basic and nucleophilic properties. Potassium alkoxides assist alkyllithium in the metalation of hydrocarbons in Lochmann-Schlosser-bases. Both compounds form mixed aggregates, which enhance the thermal stability, solubility, and the basic reactivity of these mixtures. A very unusual spherical mixed alkoxy aggregate was discovered by Grützmacher et al., where a central dihydrogen phosphide anion is surrounded by a highly dynamic shell of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 94 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…It is known that variable encapsulation could cause different intriguing structural effects. 77 Remarkably, the same peculiarity for cage-like mixed-valent manganese complexes encapsulating any anions is realized in complex 4 , i.e. , the inner hydroxyl anion is linked only to the Mn III ions.…”
Section: Resultsmentioning
confidence: 87%
“…It is known that variable encapsulation could cause different intriguing structural effects. 77 Remarkably, the same peculiarity for cage-like mixed-valent manganese complexes encapsulating any anions is realized in complex 4 , i.e. , the inner hydroxyl anion is linked only to the Mn III ions.…”
Section: Resultsmentioning
confidence: 87%
“…These examples demonstrated that a range of smaller and larger, linear, or planar anionic units can be accommodated in the surrounding cationic [Na 13 (O t Bu) 12 + ] environment. The lower threshold in this molecular construction has already been determined: fluoride 8 and hydroxide 7 prefer arrangements reduced by two NaO t Bu units: Na 11 (O t Bu) 10 X (X = OH or F).…”
mentioning
confidence: 84%
“…These values are close to those of the compounds CH 3 @1 and Br@1 . 8 The respective central anions CH 3 − and Br − are considerably smaller than BF 4 − , but the overall molecular size of BF 4 @1 is almost the same. This is contrary to the trend observed for other central anions and the size of their corresponding alkoxide hull.…”
mentioning
confidence: 96%
See 2 more Smart Citations